The Legend of the Jade Phoenix. - Thurston, Robert (New York : Penguin, 2003)
In the thirty-first century, the BattleMech is the ultimate war machine--an unstoppable engine of destruciton. And the clans are the ultimate warriors, high-tech soldiers genetically engineered to be the most fearsome BattleMech pilots of all.
Adult
Keywords: "Ways of the Clan"; "Bloodname"; "Falcon Guard"